ACTIVIVE PHENOMENA OBSERVED IN ATMOSPHERIC LINES OF THE HERBIG AE STAR HD163296 - Pogodin, M. A.; Guimaraes, M. M.; Alencar, S. H.P.; Corradi, W. J.B.; Vieira, S. L.A. (Одеські астрономічні публікації, 2008)
We present new results of a high- resolution spectroscopic investigation of the young Ae Herbig star HD163296. Nineteen spectra of this object had been obtained on May 8 - 10, 2002 at the ESO with the FEROS high-resolution echelle spectrometer (R=48000) installed at the 1.52m telescope. We have revealed a variability in a number of atmospheric lines of some ionized metals. This variability correlates with spectral parameters connected with the accretion process. In the night on May 8 a correlation of the atmospheric activity with the intensity of the outflowing matter was also observed. An interpretation of these phenomena is considered in the framework of several model.